2014
DOI: 10.1016/j.catena.2013.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation and soil organic carbon fractions under different land uses on the tableland of the Loess Plateau of China

Abstract: Land uses and cultivation are important factors controlling SOC storage on the Loess Plateau. These factors may also affect the relative importance of different mechanisms for the stabilization of organic matter in the soil. Easily oxidizable organic carbon (EOC), aggregation and aggregate C fractions in the soil were measured under different land uses. Aggregates were fractionated using a wet-sieving procedure to obtain the distribution of water-stable aggregates. The fractions of aggregates, aggregate SOC an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(59 citation statements)
references
References 43 publications
(48 reference statements)
7
50
0
2
Order By: Relevance
“…SOC played a significant role in the improvement of the physicochemical properties of the soil and the formation of soil aggregates [47,48]. Our results are in line with similar findings of other researchers [49][50][51][52][53][54][55] and demonstrate that grassland contains a high amount of SOC and a significantly higher SOC content was observed in AAO. This is perhaps due to slightly higher WSA, GMD, and MWD in AAO and GL compared to the other types of land use.…”
Section: Differences In Soc Between Different Land-use Systemssupporting
confidence: 92%
“…SOC played a significant role in the improvement of the physicochemical properties of the soil and the formation of soil aggregates [47,48]. Our results are in line with similar findings of other researchers [49][50][51][52][53][54][55] and demonstrate that grassland contains a high amount of SOC and a significantly higher SOC content was observed in AAO. This is perhaps due to slightly higher WSA, GMD, and MWD in AAO and GL compared to the other types of land use.…”
Section: Differences In Soc Between Different Land-use Systemssupporting
confidence: 92%
“…In the present study, soil bulk density was mean values obtained from eight common pedo-transfer functions (Xu et al 2015). Mean weight diameter (MWD), geometric mean diameter (GMD), percentage of > 0.25 mm water stable aggregates (R 0.25 ), structure deterioration rate (SDR), index of unstable aggregates (E LT ), and stability ratio of water stable aggregate (WSAR) were calculated according to the methods described by Fan et al (2010), Gupta Choudhury et al (2014), and Liu et al (2014a). The ratios of alkyl C/O-alkyl C, aliphatic C/aromatic C, and hydrophobic C/ hydrophilic C were calculated according to the method of Zhang et al (2011).…”
Section: Calculations and Statistical Analysismentioning
confidence: 99%
“…As expected, MWD, GMD, R 0.25 , SDR, E LT and WSAR were significantly correlated with each other (Table 6). A larger MWD, GMD, R 0.25 and WSAR and a smaller SDR and E LT indicated the stability of soil aggregates was higher (Fan et al 2010;Gupta Choudhury et al 2014;Liu et al 2014a). Thus, our results (Table 3) suggested that the stability of soil water-stable aggregates was the highest for alpine meadow, followed by alpine steppe and alpine desert.…”
Section: Soil Aggregate Stabilitymentioning
confidence: 99%
“…However, recent work illustrates that the fraction of SOC determined by permanganate appears to contribute primarily to SOC sequestration, whereas a closer correspondence to nutrient availability in the short term is shown by the SOC fraction disposed to mineralization during incubation studies [47]. Similarly, the fraction of SOC oxidized with dichromate was associated with larger aggregates of grassland and forest, rather than the small aggregates of croplands [48]. Use of density fractions and size fractions to characterize SOC from recent residue inputs shows that the nitrogen concentration and nitrogen availability of the SOC are affected by not only the fractionation method, but also by the quality and placement of the residue and by the environmental conditions that speed or slow the breakdown [49].…”
Section: Discussionmentioning
confidence: 99%